The Factors that Influence Individual Taxpayer Compliance in the Implementation of the Coretax System - Anne Andyani Pratiwi; Sofie; Kanitsorn Terdpaopong (Journal of Economics and Business UBS, 2026)
This study examines the effects of taxpayer awareness, moral obligation, tax understanding, and the Coretax System on individual taxpayer compliance, with tax socialization serving as a moderating variable and income level as a control variable. Using purposive sampling, data were collected from 224 individual taxpayers residing in the Greater DKI Jakarta area through a questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to evaluate both the measurement model and the structural model. The findings reveal that taxpayer awareness and tax understanding have positive and significant effects on individual taxpayer compliance. In contrast, the Coretax System and moral obligation do not significantly influence compliance behavior. Income level, included as a control variable, is found to be positively associated with individual taxpayer compliance. The results further indicate that tax socialization does not moderate the relationships between the independent variables and individual taxpayer compliance, suggesting that it neither strengthens nor weakens these relationships. These findings imply that improving taxpayer awareness and tax knowledge can enhance compliance. However, this study is limited by its reliance on self-administered questionnaires, which may have introduced misunderstandings and response bias. Future research should consider supervised data collection methods and explore additional factors influencing taxpayer compliance.